DEVELOPMENT AND VALIDATION METHOD OF CYCLOPHOSPHAMIDE AND 4-HYDROXYCYCLOPHOSPHAMIDE WITH 4-HYDROXYCYCLOPHOSPHAMIDE-D4 AS INTERNAL STANDARD IN DRIED BLOOD SPOTS USING UPLC-MS/MS - HASANAH, YESI IHDINA FITYATAL; HARAHAP, YAHDIANA; SURYADI, HERMAN (International Journal of Applied Pharmaceutics, 2021)
Objective: Cyclophosphamide (CP) is anticancer of the alkylating agent (nitrogen mustard) and a prodrug which will be metabolized into an active metabolite form, 4-hydroxycyclophosphamide (4-OHCP). Therefore, the effectiveness of therapy with CP is determined by its metabolites concentration. The purpose of this study was to obtain a validated analytical method of CP and 4-OHCP simultaneously and sensitively in dried blood spots with SIL (Stable Isotope Labeled) 4-OHCP-d4 as the internal standard using liquid chromatography-tandem mass spectrometry, so optimization and full validation are conducted in this research. Methods: A simpler analytical method was developed and validated to quantify CP and 4-OHCP in DBS samples using an Ultra-High-Performance Liquid Chromatography-Tandem Mass Spectrometry (UPLC-MS/MS). A linear regression was used as the statistical analysis method. Sample preparation was performed by protein precipitation using methanol. The separation was performed on UPLC H-Class BEH C18 column using formic acid 0.01%-acetonitrile as the mobile phase in gradient mode at 0.2 ml/minute. The mass detection was performed on Waters Xevo TQD using ESI+for CP, 4-OHCP-SCZ, and IS 4-OHCP-d4-SCZ with m/z value: 261.03>140.16; 334.10>221.04; and 338.10>225.06. Results: This method was linear within the range of 10–40,000 ng/ml for CP and 5–4,000 ng/ml for 4-OHCP. Lower Limit of Quantification (LLOQ) concentration of CP was 10 ng/ml and 4-OHCP was 5 ng/ml. Conclusion: This method has successfully fulfilled the validation requirement referring to the 2011 EMA and 2018 FDA guidelines.